Agronomic Performance of Corn Silage Intercropped with Urochloa Ruziziensis (JOURNAL OF ADVANCES IN AGRICULTURE, 2022)
The integrated cultivation of corn with forages leads to competition for production factors such as water, light and nutrients however, currently, it is being practiced to improve the chemical, physical and biological characteristics of the soil, in addition to increasing grain and straw production for the next crop. In this sense, the objective of this work was to evaluate the agronomic performance of corn silage intercropped with the species Urochloa ruziziensis. The experiment was carried out on a rural property located in the municipality Abadia dos Dourados - Minas Gerais, Brazil. A randomized block design was used with two treatments (corn cultivated with and without intercropping with U. ruziziensis) and ten replications. The evaluations in the corn crop were carried out at 100 days after planting. The variables analyzed were: plant height, corn cob insertion height, corn cob weight and corn cob size. Data were selected for analysis of variance and level means of Tukey test models at 5% probability test. Urochloa ruziziensis when intercropped with a corn hybrid increased the height of the corn cob insertion, the size and weight of the corn cob reaching satisfactory levels.